Trinidad - (:unkn) unknown (My University, 2009)
A picture of a dirt road line on both sides with coconut trees leading to the ocean.
Colour; Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Coasts; Coconut palm; Roads